Glufosinate Effects on Nitrogen Nutrition, Growth, Yield, and Seed Composition in Glufosinate-Resistant and Glufosinate-Sensitive Soybean - Krishna N. Reddy; Robert M. Zablotowicz; Nacer Bellaloui; Wei Ding (International Journal of Agronomy)
Glufosinate applied to glufosinate-resistant crops may drift and injure glufosinate-sensitive crops. A 2-yr field study examined glufosinate effects on plant injury, chlorophyll content, nodulation, nitrogenase activity, leaf nitrogen, yield, and seed composition in soybean. Glufosinate drift was simulated by application at 45 g/ha to glyphosate-resistant and conventional (glufosinate-sensitive) soybean at 3 weeks after planting (WAP). Glufosinate effects were also evaluated in glufosinate-resistant soybean at 450 g/ha applied twice at 3 and 6 WAP. In glufosinate-resistant soybean, chlorophyll, nitrogenase activity, root respiration, plant biomass, and yield were not affected; seed nitrogen and protein were increased; seed oil content decreased. In glufosinate-sensitive soybean, glufosinate caused 28-32% injury and decreased 35-42% chlorophyll content within 3 d after treatment (DAT) but soybean completely recovered by 14 DAT. Glufosinate had no effect on plant biomass, nitrogenase activity, and root respiration in 2009 and inconsistent effects in 2010. In glufosinate-sensitive soybean, glufosinate had no effect on yield; increased leaf nitrogen, seed protein, and oleic acid; decreased oil content, linoleic, and linolenic acid. Glufosinate-sensitive soybean exposed to glufosinate drift may exhibit transient injury but soybean could recover without a yield penalty. Glufosinate altered seed composition in all soybean types.